Non-Fellowship regional anesthesia training and assessment: an international Delphi study on a consensus curriculum. Issue 10 (20th July 2021) - Chuan, Alwin; Jeyaratnam, Bahaven; Fathil, Shah; Ferraro, Leonardo HC; Kessow, Aneet; Lim, Yean Chin; O'Rourke, Michael J; Ponde, Vrushali; Raft, Julien; Segurado, Arthur; Tangwiwat, Suwimon; Torborg, Alexandra; et al.
Abstract : Background and objectives: While there are several published recommendations and guidelines for trainees undertaking subspecialty Fellowships in regional anesthesia, a similar document describing a core regional anesthesia curriculum for non-fellowship trainees is less well defined. We aimed to produce an international consensus for the training and teaching of regional anesthesia that is applicable for the majority of worldwide anesthesiologists. Methods: This anonymous, electronic Delphi study was conducted over two rounds and distributed to current and immediate past (within 5 years) directors of regional anesthesia training worldwide. The steering committee formulated an initial list of items covering nerve block techniques, learning objectives and skills assessment and volume of practice, relevant to a non-fellowship regional anesthesia curriculum. Participants scored these items in order of importance using a 10-point Likert scale, with free-text feedback. Strong consensus items were defined as highest importance (score ≥8) by ≥70% of all participants. Results: 469 participants/586 invitations (80.0% response) scored in round 1, and 402/469 participants (85.7% response) scored in round 2. Participants represented 66 countries. Strong consensus was reached for 8 core peripheral and neuraxial blocks and 17 items describing learning objectives and skills assessment. Volume of practice for peripheral blocks was uniformly 16–20 blocks per anatomical region, while ≥50 neuraxial blocks were considered minimum. Conclusions: This international consensus study provides specific information for designing a non-fellowship regional anesthesia curriculum. Implementation of a standardized curriculum has benefits for patient care through improving quality of training and quality of nerve blocks.